The effectiveness of motivational interviewing on resilience, sense of purpose, and social interest among adolescent girls in middle school - F. Ghasemi Niaei; N. Derakhshan (Психологическая наука и образование)
Objective. The present study aims to investigate the effectiveness of motivational interviewing in enhancing resilience, sense of purpose, and social interest among adolescent girls in middle school (ages 13–14). Methods. This study employed a quasi-experimental design with a pre-test/post-test and a control group. The tools used in this study included the Connor-Davidson Resilience Scale, Crumbaugh and Maholick’s Purpose in Life Test, and Crandell’s Social Interest Scale. Data analysis was performed using multivariate analysis of covariance (MANCOVA). Results. The findings suggest that motivational interviewing significantly enhances adolescent girls' sense of purpose during the intervention phase (ηp² = 0,473) and follow-up phase (ηp² = 0,378). It also improves their resilience during the intervention phase (ηp² = 0,247) and follow-up phase (ηp² = 0,205). Furthermore, motivational interviewing is effective in increasing adolescent girls' social interest during the intervention phase (ηp² = 0,203) and follow-up phase (ηp² = 0,109). Conclusions. Overall, motivational interviewing can strengthen adolescents' resilience against challenges, foster a sense of purpose, and serve as a foundation for social interest, increased empathy, and greater social participation.